2005
DOI: 10.1089/vbz.2005.5.237
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid Requirements for Infection of Ticks byBorrelia burgdorferi

Abstract: Borrelia burgdorferi strain B31 MI commonly loses one or more of its complement of 21 extrachromosomal plasmids during normal handling procedures and during genetic manipulations. Certain plasmid losses cause an inability or reduction in the ability of spirochetes to infect mice. In the current study, nine strains of spirochetes with varying plasmid profiles were used to identify plasmids necessary for nymphal tick infection. Nymphal ticks were artificially fed the nine spirochete strains as well as the parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 33 publications
1
45
0
Order By: Relevance
“…Other studies have demonstrated that individual plasmids have determinants important in infecting both ticks and mice. Spirochetes without lp28-4 are associated with an attenuation of the spirochetes' ability to infect tick guts and mice (12,13,20,26). The gene(s) on lp25 besides BBE22 that is responsible for long-term persistence in ticks is not known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have demonstrated that individual plasmids have determinants important in infecting both ticks and mice. Spirochetes without lp28-4 are associated with an attenuation of the spirochetes' ability to infect tick guts and mice (12,13,20,26). The gene(s) on lp25 besides BBE22 that is responsible for long-term persistence in ticks is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, B. burgdorferi lacking lp25 is unable to infect mice when injected intraperitoneally (12,13,20). Linear plasmid 25 also has a role in infecting nymphal ticks; spirochetes lacking lp25 are associated with reduced gut infectivity (26).…”
mentioning
confidence: 99%
“…The process of generating mts may inadvertently result in selection of mutations in distal genes or loss of plasmids with significant effects on the infectivity of B. burgdorferi (36,41,51,64). There were no overt differences in the protein profile and the level of OspC was significantly higher under mammalian host-specific conditions in all three strains, indicating that both the regulatory mechanisms and the expression of other critical determinants of virulence were similar and intact in the mt and control strains (1,58,63,67).…”
mentioning
confidence: 96%
“…IMMUN. (52,64,65). Nonetheless, generation of mts using this approach facilitated analysis of the effect of loss of one or more genes in the infectivity of B. burgdorferi for the mammalian host.…”
mentioning
confidence: 99%
“…Moreover, cp26 plasmid carries a gene coding for outer surface protein C (OspC), which is necessary for early stage of vertebrate host infection but is not required during growth in the tick vector or during in vitro growth [86][87][88] . Strother et al 89 tried to identify plasmids of B. burgdorferi required for tick infection. They demonstrated that plasmids lp5, lp28-1, and cp9 are not required for tick infection, whereas loss of lp25 and lp28-4 is associated with reduced tick infectivity.…”
Section: Genome Structurementioning
confidence: 99%